Highly Sensitive Quantification of Plasma Severe Acute Respiratory Syndrome Coronavirus 2 RNA Sheds Light on its Potential Clinical Value. (17th August 2020) - Veyer, David; Kernéis, Solen; Poulet, Geoffroy; Wack, Maxime; Robillard, Nicolas; Taly, Valérie; L'Honneur, Anne-Sophie; Rozenberg, Flore; Laurent-Puig, Pierre; Bélec, Laurent; Hadjadj, Jérôme; Terrier, Benjamin; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) is a global public health problem that has already caused more than 662 000 deaths worldwide. Although the clinical manifestations of COVID-19 are dominated by respiratory symptoms, some patients present other severe damage such as cardiovascular, renal and liver injury, and/or multiple organ failure, suggesting a spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in blood. Recent ultrasensitive polymerase chain reaction (PCR) technology now allows absolute quantification of nucleic acids in plasma. We intend to use the droplet-based digital PCR technology to obtain sensitive detection and precise quantification of plasma SARS-CoV-2 viral load (SARS-CoV-2 RNAemia) in hospitalized COVID-19 patients. Methods: Fifty-eight consecutive COVID-19 patients with pneumonia 8 to 12 days after onset of symptoms and 12 healthy controls were analyzed. Disease severity was categorized as mild to moderate in 17 patients, severe in 16, and critical in 26. Plasma SARS-CoV-2 RNAemia was quantified by droplet digital Crystal Digital PCR next-generation technology (Stilla Technologies, Villejuif, France). Results: Overall, SARS-CoV-2 RNAemia was detected in 43 (74.1%) patients. Prevalence of positive SARS-CoV-2 RNAemia correlated with disease severity, ranging from 53% in mild-to-moderate patients to 88% in critically ill patients ( P = .036). Levels of SARS-CoV-2 RNAemia were associated with severity ( P = .035). Among 9 patients who experienced clinical deterioration during follow-up, 8 had positive SARS-CoV-2 RNAemia at baseline, whereas only 1 critical patient with undetectable SARS-CoV-2 RNAemia at the time of analysis died at day 27. Conclusion: SARS-CoV-2 RNAemia measured by droplet-based digital PCR constitutes a promising prognosis biomarker in COVID-19 patients. Abstract : Plasma severe acute respiratory syndrome coronavirus 2 RNAemia quantified by droplet-based digital polymerase chain reaction is correlated with clinical severity of coronavirus disease 2019 (COVID-19) and constitutes a promising prognosis biomarker to monitor in hospitalized COVID-19 patients.